Liquidity and Profitability of Capital Structure in the Consumer Goods Industry on The Indonesia Stock Exchange - Retnowati Jasa; Roy Rocky Suprapto Baan; Budiawan (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze how liquidity (Quick Ratio) and profitability (Return on Assets, Return on Equity, and Net Profit Margin) affect the capital structure of consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023 and to provide empirical evidence regarding the applicability of capital structure theories, particularly the Pecking Order Theory, in the Indonesian consumer goods industry. This research employed a quantitative approach using secondary data from annual reports of consumer goods companies published on the IDX website. Out of a population of 57 firms, a purposive sampling method selected 10 companies operating in the food and beverage, cigarette, and pharmaceutical sub-sectors, based on the completeness and consistency of their financial statements. The data were analyzed using multiple linear regression, supported by classical assumption tests including normality, multicollinearity, autocorrelation, and heteroscedasticity to ensure the model's robustness. The data indicates that liquidity (Quick Ratio) and profitability (Return on Assets) have a negative and significant impact on capital structure, while Return on Equity shows a positive and significant effect. Net Profit Margin, however, does not significantly influence capital structure. Overall, liquidity and profitability account for 54.6% of the variation in capital structure, with the remaining influenced by other factors beyond the scope of this study. The findings highlight the importance of liquidity and profitability in guiding corporate financing decisions. They support the Pecking Order Theory and emphasize the need for firms to adopt a balanced financing approach that leverages both internal resources and external debt to promote financial stability and sustainable growth.